Imitation and innovation (2008)
The main subject of this research is to understand in what moment is appropriate for a firm to innovate according to the cycle of the industry; at what peace it has to be takingthe innovation as a competition tool; and in what moment appear followers of these pioneers. Finally, there is a porpoise of a method that could be used for measure the innovation in an industry, specifically by the quantity invested in innovation and development.